2018
DOI: 10.1111/tops.12339
|View full text |Cite
|
Sign up to set email alerts
|

Repair: The Interface Between Interaction and Cognition

Abstract: Conversational repair is the process people use to detect and resolve problems of speaking, hearing, and understanding. Through repair, participants in social interaction display how they establish and maintain communication and mutual understanding. We argue that repair provides a crucial theoretical interface for research between diverse approaches to studying human interaction. We provide an overview of conversation analytic findings about repair in order to encourage further cross-disciplinary research inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
46
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 103 publications
0
46
0
1
Order By: Relevance
“…They are primarily analyzed in terms of where in the sequence of turns in a conversation trouble is signaled, who (nominally) produced the source of the trouble, who responded to it, and where in the sequence it is resolved. Albert and de Ruiter () and Purver, Hough, and Howes () provide examples and further explanation of these structures.…”
Section: The Cognitive Science Of Miscommunicationmentioning
confidence: 96%
See 1 more Smart Citation
“…They are primarily analyzed in terms of where in the sequence of turns in a conversation trouble is signaled, who (nominally) produced the source of the trouble, who responded to it, and where in the sequence it is resolved. Albert and de Ruiter () and Purver, Hough, and Howes () provide examples and further explanation of these structures.…”
Section: The Cognitive Science Of Miscommunicationmentioning
confidence: 96%
“…However, the most developed empirical account of what happens when things go wrong comes from conversation analysis (CA), a sociological tradition built on detailed qualitative analyses of natural interaction (Sacks, ). For reasons that are explored further below, the relationship between conversation analysis and cognitive science is not straightforward (see also De Ruiter & Albert, ; and the discussion by Albert & de Ruiter, ) but it has had a significant influence on work in mainstream cognitive science (viz: Clark & Marshall, ; Levelt, ; Levinson, ; Hutchins, ; Healey, ) and is a key reference point for all the papers in this volume.…”
Section: The Cognitive Science Of Miscommunicationmentioning
confidence: 99%
“…These cross-disciplinary initiatives build on the successful model of 'naturalistic experiments' (Heath & Luff, 2017) exemplified here by Heritage et al (2007). This article aims to encourage many more such cross-overs by providing an overview of key research procedures that can work as practical methodological interfaces between conversation analytic and experimental methods for human interaction research within psychology and cognitive science (Albert & de Ruiter, 2018;De Jaegher, Peräkylä, & Stevanovic, 2016;De Ruiter & Albert, 2017). 9 In this paper we have suggested that researchers in the field of human interaction can enhance the reproducibility and reliability of their findings by grounding their theories in the details of the interactional ' context of discovery'.…”
Section: Conclusion: Ecological Grounding For Greater Reproducibilitymentioning
confidence: 99%
“…This article aims to encourage many more such cross-overs by providing an overview of key research procedures that can work as practical, methodological interfaces between conversation analytic and experimental methods for studying human interaction within psychology and cognitive science (Albert & de Ruiter, 2018;De Jaegher, Peräkylä, & Stevanovic, 2016;De Ruiter & Albert, 2017) 9 In this paper we have suggested that researchers in the field of human interaction can enhance the reproducibility and reliability of their findings by grounding their theories in the details of the interactional 'context of discovery'. To achieve this, we recommend researchers devote attention and resources to exploring this context in an empirically constrained way by limiting their theorizing to phenomena and resources that are observable to both analysts and participants.…”
Section: Conclusion: Ecological Grounding For Greater Reproducibilitymentioning
confidence: 99%